Characterization of natural genetic variations affecting tomato cell competence to assume different developmental fates - Pinto, Maísa de Siqueira (2016)
The study of natural genetic variations affecting organogenic capacity in tomato (Solanum lycopersicum) is attractive due to the existence of several tomato wild relatives with enhanced organogenic capacity. The characterization of such variations is relevant not only in order to manipulate plant development, but also to understand its ecological and evolutionary significance. The objective of this work was to characterize three tomato loci whose alleles from the wild relative S. pennellii enhance in vitro shoot and root regeneration, and analyze their involvement in the acquisition of competence phase. In the first manuscript, we report the genetic and physiological characterization of the loci Rg3C, Rg7H and Rg8F. The S. pennellii alleles were introgressed into the tomato genetic model cv. Micro-Tom (MT), creating the near isogenic lines (NILs) MT-Rg3C, MT-Rg7H and MT-Rg8F. In the second manuscript we present a comparative analysis between the Near-Isogenic Lines (NILs) MT-Rg3C and MT-Rg1. Since Rg1 was proposed to be a key gene in the acquisition of competence, and was mapped in the chromosome three, it is believed that Rg3C is probably equivalent to the Rg1 allele from S. peruvianum. After the introgression of the loci into the MT background, the NILs presented enhanced regeneration of both roots and shoots, confirming that the loci were successfully introgressed. The analysis of the time for acquisition of competence and induction, together with the molecular characterization of the NILs, indicate that the genes present in the loci Rg3C, Rg7H and Rg8F affect in vitro regeneration by distinct pathways. While Rg3C decreased the time required for both acquisition of competence and induction, the other loci seem to influence only the time of acquisition of competence, in the case of Rg8F, or the time of induction, in the case of Rg7H. Additionally, although MT-Rg3C has an enhanced shoot branching phenotype, MT-Rg7H and MT-Rg8F did not differ from MT in this trait. This indicates that enhanced in vitro shoot formation in tomato is not necessarily related to a deleterious high branching phenotype. Comparative analyses of MT-Rg1 and MT-Rg3C strongly indicate that Rg1 and Rg3C are alleles of a same gene controlling regeneration capacity. Integrating Rg1 and Rg3C mapping information, we were able to narrow the number of candidate genes for Rg1/Rg3C to only 27, which were also analyzed and discussed.